Cell & Molecular Biology of Prostate Cancer Updates, Insights and New Frontiers (Advances in Experimental Medicine and Biology,, 2018)
This volume covers classic and modern cell and molecular biology of prostate cancer, as well as novel biomarkers, inflammation, centrosome pathologies, microRNAs, cancer initiation novel biomarkers, inflammation, centrosome pathologies, microRNAs, cancer initiation and genetics, epigenetics, mitochondrial dysfunctions and apoptosis, cancer stem cells, angiogenesis and progression to metastasis, and treatment strategies including clinical trials related to prostate cancer. Cell & Molecular Biology of Prostate Cancer is one of two companion books comprehensively addressing the biology and clinical aspects of prostate cancer. Prostate Cancer: Molecular & Diagnostic Imaging and Treatment Stategies, the companion volume, discusses both classic and the most recent imaging approaches including analysis of needle biopsies, applications of nanoparticle probes and peptide-based radiopharmaceuticals for detection, early diagnosis and treatment of prostate cancer. Taken together, these volumes form one comprehensive and invaluable contribution to the literature. .